5(x+3)+3(x-1)=-9

Simple and best practice solution for 5(x+3)+3(x-1)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+3(x-1)=-9 equation:


Simplifying
5(x + 3) + 3(x + -1) = -9

Reorder the terms:
5(3 + x) + 3(x + -1) = -9
(3 * 5 + x * 5) + 3(x + -1) = -9
(15 + 5x) + 3(x + -1) = -9

Reorder the terms:
15 + 5x + 3(-1 + x) = -9
15 + 5x + (-1 * 3 + x * 3) = -9
15 + 5x + (-3 + 3x) = -9

Reorder the terms:
15 + -3 + 5x + 3x = -9

Combine like terms: 15 + -3 = 12
12 + 5x + 3x = -9

Combine like terms: 5x + 3x = 8x
12 + 8x = -9

Solving
12 + 8x = -9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 8x = -9 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = -9 + -12
8x = -9 + -12

Combine like terms: -9 + -12 = -21
8x = -21

Divide each side by '8'.
x = -2.625

Simplifying
x = -2.625

See similar equations:

| X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 | | 4x+14=112-10x | | 4x^2+3x-7=2x-2 | | 9-5p= | | 3b+7=52 | | 10r-12=-28 | | f=(g-h+k)/5 | | y=-2/2+2 | | F(x)=4x^2-x-3 | | 22x-18=36+16x | | 2m+15=-23 | | -3y-5=-2 | | 8(x+6)+5=8x+5 | | x-7.1=5.4 | | 4x-9=6-13 | | z+37=14 | | 0.6x+1.9x= |

Equations solver categories